AN EXPERIMENT IN ARCTIC VLF NAVIGATION. - Redell, Karl R. (1965)
The passage of ice island ARLIS II into the East Greenland Sea early in 1965 and the resulting higher drift rate made necessary a more continuous type of navigation than was possible with celestial navigation. An experimental VLF system was available which could theoretically provide navigational accuracies of plus or minus 2 miles. Three VLF stations (GBR, NSS, and NPG) were received on the island. The VLF phase tracking data was in error, however, due to defective preset counters in the frequency synthesizers. Operational problems and potentials of the system in Arctic use are discussed. (Author)